Arahan Do Not Resuscitate (DNR) menurut perspektif hukum Islam / Mohammad Mustaqim Malek - Mohammad Mustaqim , Malek (2018)
Different types of medical treatments and technology were developed to treat diseases. However, limitation came into the picture when the illnesses have reached to the advanced stage. Treatment such as resuscitation and life support only serves to prolong the life of the patient without any benefits of recuperation. Therefore, consideration to withhold resuscitation from the patient in the event of cardiopulmonary and respiratory arrest, in order to enable the death to occur naturally arises. This action is known as Do Not Resuscitate (DNR) Order. Currently, there is lack of standard guidelines regarding DNR in the light of Islam. There are Islamic issues regarding its implementation factors, namely: (1) medical futility, (2) family financial constraint and limitation of medical facilities, and (3) patient’s autonomy. Hence, this research aims to: (1) explain the concept of DNR Order and the factors of its implementation, (2) implement takyif fiqhi on DNR Order with the methods of syarak, and (3) suggest Islamic views pertaining to the issues of DNR Order. In order to achieve the objectives, a qualitative research was conducted to collect data through literature method and in-depth interview with experts, involving those in the field of end-of-life care and in Islamic jurisprudence. The data were analyzed the methods of deduction, induction, and comparison in order to propound Islamic views towards the issues in implementing DNR order. According to the findings, the researcher found that Islam does recognize the execution of DNR order when the medical situation reaches futility stage. This is based on the priority to stop treatment when the benefits are ceased to exist. Islam also recognizes the act of withholding resuscitation for patients with no hope of recovery in order to allow other viable patients to receive the same treatment. This is also due to the burden on the next of kin to continuously finance the costs of patient care. With regards to patient’s autonomy, Islam permits the patient to request for DNR Order given his futile situation. This is based on the concept of medical consent in Islam. The researcher concluded that DNR order is permissible based on the factors mentioned above.